2016
DOI: 10.1016/j.jcgg.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence in the elderly

Abstract: a b s t r a c tMedication adherence is a crucial component in the treatment of chronic diseases. In the elderly, clinicians are faced with a unique set of problems associated with adherence that they may not have been adequately trained for. In this paper, we demonstrate the importance of medication adherence in the elderly through a case study. The different factors affecting medication adherence in the elderly are highlighted: patient, medication, health care providers, health care system, and socioeconomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
1
18

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 43 publications
4
114
1
18
Order By: Relevance
“…Patients with dementia or mild cognitive impairment may have medications administered by a caregiver and thus less likely to self-discontinue. 31 In addition, patients with dementia or mild cognitive impairment may also be less likely to discontinue therapy if they are taking an acetylcholinesterase inhibitor, which may cause worsening urinary symptoms. 32 We also found that paralysis was associated with decreased risk of discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with dementia or mild cognitive impairment may have medications administered by a caregiver and thus less likely to self-discontinue. 31 In addition, patients with dementia or mild cognitive impairment may also be less likely to discontinue therapy if they are taking an acetylcholinesterase inhibitor, which may cause worsening urinary symptoms. 32 We also found that paralysis was associated with decreased risk of discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…In geriatric training, comprehensive geriatric assessment is taught, and these holistic assessments take into account medications and their uses. Understanding the use of these tools will allow medical professionals to be more proficient, and be able to carry out assessment of medication adherence as part of their daily routine …”
Section: Introductionmentioning
confidence: 99%
“…Understanding the use of these tools will allow medical professionals to be more proficient, and be able to carry out assessment of medication adherence as part of their daily routine. 10,11 Our search of the literature showed that for the past 6 years, there have been no studies that provide a complete review of the literature in this area. 7 Hence, the aim of the present article was to provide a systematic review of the current literature on the factors affecting medication adherence in the geriatric population.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising as older patients are prone to multiple comorbidities, and thus more likely to take multiple medications, and therefore may have a higher risk of nonadherence compared to younger patients [11]. We also found the average interval on weekends has more variation than weekdays.…”
Section: Data Analysis and Resultsmentioning
confidence: 53%